LEARN: a multicentre, cross‐sectional evaluation of Urology teaching in UK medical schools. (26th May 2022) - Ng, Alexander; V, Wai‐Shun Chan; Asif, Aqua; Light, Alexander; Lam, Chon Meng; Jayaraajan, Keerthanaa; Cambridge, William A.; Matthews, Melissa Gillian; Kulkarni, Meghana; S, Zhi Yang Ooi; Nathan, Arjun; Ahmed, Najma; et al.
Abstract : Objective: To evaluate the status of UK undergraduate urology teaching against the British Association of Urological Surgeons (BAUS) Undergraduate Syllabus for Urology. Secondary objectives included evaluating the type and quantity of teaching provided, the reported performance rate of General Medical Council (GMC)‐mandated urological procedures, and the proportion of undergraduates considering urology as a career. Subjects and Methods: The uroLogical tEAching in bRitish medical schools Nationally (LEARN) study was a national multicentre cross‐sectional evaluation. Year 2 to Year 5 medical students and Foundation Year (FY) 1 doctors were invited to complete a survey between 3 October and 20 December 2020, retrospectively assessing the urology teaching received to date. Results are reported according to the Checklist for Reporting Results of Internet E‐Surveys (CHERRIES). Results: In all, 7063/8346 (84.6%) responses from all 39 UK medical schools were included; 1127/7063 (16.0%) were from FY1 doctors who reported that the most frequently taught topics in undergraduate training were on urinary tract infection (96.5%), acute kidney injury (95.9%) and haematuria (94.4%). The most infrequently taught topics were male urinary incontinence (59.4%), male infertility (52.4%) and erectile dysfunction (43.8%). Male and female catheterisation on patients as undergraduates was performed by 92.1% and 73.0% of FY1 doctors respectively, and 16.9% had considered a career in urology. Theory‐based teaching was mainly prevalent in the early years of medical school, with clinical skills teaching, and clinical placements in the later years of medical school. In all, 20.1% of FY1 doctors reported no undergraduate clinical attachment in urology. Conclusion: The LEARN Study is the largest ever evaluation of undergraduate urology teaching. In the UK, teaching seemed satisfactory as evaluated against the BAUS undergraduate syllabus. However, many students report having no clinical attachments in Urology and some newly qualified doctors report never having inserted a catheter, which is a GMC mandated requirement. We recommend a greater emphasis on undergraduate clinical exposure to urology and stricter adherence to GMC mandated procedures.